THE INFLUENCE OF WORK ETHIC AND COUNTERPRODUCTIVE WORK BEHAVIOUR OF CIVIL SERVANTS - Abdullah, Aspalaila; Halim, Fatimah Wati (Journal of Technology Management and Business, 2016)
This paper aims to look at issues related to work ethic and counterproductive work behaviour of civil servants in Malaysia. In addition, this concept paper will present theories and past studies relevant to work ethic and the counterproductive work performance in an organization either in Malaysia or abroad. The understanding about an individual ethical behaviour is explained through theories like Theory of Reasoned Action-TORA and Theory of Planned Behaviour by Fishben and Ajzen (1980). The operational work ethic in this concept paper is based upon the 12 Cardinal Work Ethic which consists of 12 work ethic important to the civil servants in Malaysia, among which are The Value of Time, The Success of Perseverance, The Enjoyment at Work, The Greatness of Simplicity, The Respectful Personality, The Strength of Kindness, The Good Example, The Obligation to Carry Out Duty, The Wisdom of Being Wise, The Importance of Patience, Talent Enhancement and The Satisfaction to Invent. Several theories such as the Social Exchange Theory, Norm of Reciprocity, Cognitive Social Theory and General Strain Theory will be further discussed. These theories with the adaptation of The Counterproductive Work Behaviour (CWB) Model by Spector (2006) categorized CWB into two categories. They are the organizational CWB, for example, sabotage, theft, work withdrawal and crimes against production, and the individual CWB, for example, personal conflict and abuse (Spector et al., 2006). Results of previous studies shows individuals who possess high work ethics relating directly with CWB. Individuals with a high work ethic will be having lowerÂ tendency to involve with CWB and on the other hand individuals who have low work ethic may tend to engage in CWB.